The Correlation of Sleep Patterns toward Student Academic Ability of the Pre-Clinic Students - Taqiyuddin, Naufal; Salsabila, Adinda Firyal; Rahmadhani, Desintya; Nabila, Jihan; Dwipo, Aryo Kusumo (International Journal of Psychosocial Rehabilitation, 2020)
Background: Some studies suggest that one-third of adults experience poor sleep habits. Students are one of them, this is because students experience stress due to academic burdens changing sleep patterns and affecting student academic ability. Objective: To determine the correlation between sleep patterns and academic abilities. Methods: The research design used was cross-sectional using a self-administered Google form questionnaire given to students of the Faculty of Dental Medicine, Universitas Airlangga, from the third and fifth semesters through social media. Results: This questionnaire was filled in by 100 respondents (49 respondents from the third-semester student and 51 respondents from the fifth-semester students). As many as 91 students had less sleep duration (<7 hours) before the exam, as many as 2 students had sleep duration more than 8 hours before the exam, and as many as 7 students slept for 7-8 hours before the exam. Conclusion: The majority of third and fifth-semester students have less sleep duration, which is less than 8 hours. Getting enough sleep at night before the exam is positively related to the final grades of Pharmacology and Therapeutics II and physiology II courses for students.